Yolk absorption efficiency and morphogenesis of the silver arawana Osteoglossum bicirrhosum (Cuvier, 1829) prelarvae at various interactions of temperature and salinity - Yuli Wahyu Tri Mulyani; Dedy Duryadi Solihin; Ridwan Affandi (Jurnal Iktiologi Indonesia, 2015)
The silver arawana Osteoglossum bicirrhosum (Cuvier, 1829) has been cultured successfully in Indonesia, but still facing obstacles especially handling on the larval life stage. Yolk-sac stage is one of the critical phases in the early development of fish. Yolk-sac larvae of silver arawana use a yolk as food supply. The yolk absorption process influenced by abiotic factors, particularly temperature and salinity. Hence, this study aimed to examine the interaction of temperature and salinity of media in order for optimal yolk-sac absorption and morphogenesis of silver arawana larvae. The research was conducted from November 2013 to January 2014 in the Laboratory of Aquatic Animal Physiology, Faculty of Fisheries and Marine Sciences, Bogor Agricultural University. The experimental design was arranged in two factors completely randomized designs, nine treatments with three replications. The first factor was the temperature consisted of 28, 30 and 32°C; the second factor was the salinity consisted of 3, 4 and 5%o. Yolk-sac larvae were reared in aquarium 40 x 30 x 30 cm3 with a density of 4 yolk-sac larvae per aquarium until the yolk was completely absorbed. Larvae were not fed during the experiment. The parameters measured were survival rate, time of yolk absorption, shrinkage rate of yolk, efficiency of yolk utilization, total length, total weight, specific weight growth rate, gradient osmotic oxygen consumption, and morphogenesis of larvae. The results showed that the silver arawana larvae reared at 28°C in combination with all levels of salinity (3, 4 and 5%o) and temperature of 30°C with a salinity of 3%o generate survival rate 100%. Meanwhile, the efficiency of yolk utilization, the fastest growth and morphogenesis were optimally at a temperature of 30°C in interaction with 3%o salinity. Abstrak Arwana silver Osteoglossum bicirrhosum (Cuvier, 1829) telah berhasil dibudidayakan di Indonesia, namun masih mengalami kendala terutama penanganan pada fase pralarva. Pralarva merupakan salah satu stadia yang rentan dalam perkembangan awal hidup ikan. Pralarva arwana silver memiliki kuning telur yang digunakan sebagai cadangan ma-kanan. Penyerapan kuning telur pralarva dipengaruhi oleh faktor abiotik terutama suhu dan salinitas. Penelitian ini ber-tujuan untuk mengkaji interaksi suhu dan salinitas media pemeliharaan agar optimal untuk penyerapan kuning telur dan morfogenesis pralarva arwana silver. Penelitian dilakukan dari bulan November 2013 hingga Januari 2014 di La-boratorium Fisiologi Hewan Air, Fakultas Perikanan dan Ilmu Kelautan, Institut Pertanian Bogor. Penelitian ini meng-gunakan rancangan acak lengkap faktorial dengan sembilan perlakuan dan masing-masing perlakuan memiliki tiga ulangan. Faktor pertama terdiri atas suhu 28, 30 dan 32°C, faktor kedua terdiri atas salinitas 3, 4 dan 5%o. Pralarva di-pelihara di dalam akuarium berukuran 40 x 30 x 30 cm3 dengan padat tebar empat ekor per akuarium, sampai kuning telur terserap di dalam tubuh. Selama pemeliharaan tidak diberikan pakan. Parameter yang diukur yaitu: kelangsungan hidup, waktu penyerapan kuning telur, laju penyusutan kuning telur, efisiensi pemanfaatan kuning telur, panjang total, bobot total, laju pertumbuhan spesifik, gradien osmotik, konsumsi oksigen, dan morfogenesis. Hasil penelitian menun-jukkan bahwa pralarva arwana silver yang dipelihara pada suhu 28°C dengan semua level salinitas (3, 4, dan 5%o) dan suhu 30°C dengan salinitas 3%o memiliki kelangsungan hidup 100%, sedangkan efisiensi pemanfaatan kuning telur, pertumbuhan optimal, dan morfogenesis tercepat pada perlakuan interaksi suhu 30°C dengan salinitas 3%o.